PENANAMAN MODERASI AGAMA DALAM PENDIDIKAN AGAMA ISLAM - Hanifah Salsabila, Unik; Saputra, Adi; Harsono, Lukman; Faruq Husein, Mochammad; Ainuzzamania, Nurdiena (Transpublika Publisher, 2021)
Islam as the largest religion embraced by the majority of Indonesians certainly has rules that refer to the benefit of Muslims. This literature review is an analysis of three journals on moderation published in 2020. Islamic Religious Education instills a moderate education, which is sourced from the Qur'an which teaches the value of justice, equality without caste, mutual respect for others and always maintaining balance, not only in religious life but also in social life. As for this kind of education model, it is very useful to produce tolerant behavior and actions. The role of religious teachers in instilling moderation in religion in every educational institution is very much needed because teachers themselves have an important role in providing a broad understanding and understanding of the Islamic religion which is rohmatan lil alamin which can appreciate differences between humans.